Comparing Income and Wealth Inequality in Pre-Industrial Economies: Lessons from 18th-Century Spain - Esteban A. Nicolini; Fernando Ramos Palencia (European Historical Economics Society (EHES), 2016)
Most research on the history of inequality in pre-industrial economies has focused on either wealth or income. Characterizing the distribution of wealth (resp., income) is problematic owing to insufficient information about the distribution's low (resp., high) end. Because the sources and methodologies differ between these two approaches, their results are not readily comparable and it is difficult to establish links between the respective distributions that result. In this paper, we shall use a unique data set for different regions of Spain circa 1750 and present results - the first for any pre-20thcentury economy - on both income and wealth distributions for the same sample of households. Information on wealth and income is derived from (respectively) probate inventories and the Ensenada Cadastre. Our main findings are that poor households are not entirely absent from the data set of inventories, that a household's position in the income distribution is strongly correlated with its position in the wealth distribution, and that increases in a household's wealth are associated with less thanproportional increases in its income.
Keywords: D31; N33; O15; 330; inequality; income; wealth; Spain; probate inventories; Ensenada Cadastre